Strategi Pembelajaran Motorik Kasar pada Anak Usia Dini Era Pandemi Covid-19 - Yahya Putra, Andhika (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2020)
This study aims to see the teacher's strategy in achieving gross motor learning goals during the Covid-19 pandemic. The type of research used is descriptive qualitative. The object of this research is the class teacher group A TK ABA Gunung Ketur Pakualaman Yogyakarta. Data interview technique by interview. The analysis of this research used Milles and Huberman. Test the validity of the data by using triangulation of sources and techniques. The results showed application of learning strategies is carried out, namely first, by making gross motoric learning videos then sharing them through the WhatsApp group. Second, using direct video calls with a race in it and the third, giving freedom to children to search for gross motor movement videos on YouTube. Obstacles in learning are slow parental response, bad signals, limited internet quota. For this reason, the teacher carries out home visit solutions to the homes of parents of students who have problems in the learning process.